Do Organizational Culture and Human Resources Management Practices Decrease Turnover Intention in Microfinance Company? - Sri Maryati; Nurmala Katrina Panjaitan; Anggraini Sukmawati (Binus Business Review, 2022)
Organizational culture can be interpreted as an accumulation of basic assumptions, practices, principles, beliefs, norms, and values that govern a person’s behavior and action in an organization. Microfinance Institutions (MFIs) in Indonesia are growing very fast which is not accompanied by availability of sufficient competent human resources in this financial industry. This condition has caused employee turnover which tends to increase in the last three years. The research aimed to analyze the organizational culture designed by the company manager compared to the organizational culture according to employee perception and the effect of organizational culture and Human Resources Management (HRM) Practices run by the company on employee turnover intention. The research was a case study in PT DMS, one of MFIs in Indonesia. Primary data were collected from 249 respondents using the census method as a sampling technique. Then, the analysis of organizational culture using the Organizational Culture Assessment Instrument (OCAI) analysis showed that the culture that could be applied was the type of clan. The Structural Equation Model (SEM) analysis shows that organizational culture positively affects satisfaction with the implementation of HRM practices. However, organizational culture has a negative impact on turnover intention. Then, satisfaction with implementing HRM practices has a significant and negative effect on turnover intention. It can be concluded that to decrease turnover intention, companies need to increase employee satisfaction with the implementation of organizational culture and HRM practice, such as creating employee development program.